Meeting at the 'Ijsclubterrein' in the Linnaeuspark. Ankersmit is speaking. Behind him Wibaut and Van Kol. See also A40/986
Meeting at the 'Ijsclubterrein' in the Linnaeuspark. Ankersmit is speaking. Behind him Wibaut and Van Kol. See also A40/986.